A 100 m.y. record of volcanic arc evolution in Nicaragua. (27th April 2020) - Flores, Kennet E.; Gazel, Esteban
Abstract: The processes that result in arc magmas are critical to understanding element recycling in subduction zones, yet little is known about how these systems evolve with time. Nicaragua provides an opportunity to reconstruct the history of a volcanic arc since the Cretaceous. Here we present the stratigraphy of the Cretaceous–Eocene volcanic units in Nicaragua and their relationship to the different tectonic units where the arc developed. We discovered an evolution from an arc‐dominated by calc‐alkaline compositions in the Cretaceous–Eocene, to transitional compositions in the Oligocene–Miocene, to finally tholeiitic magmas common in the modern volcanic front. Our petrographic studies confirm that in the Cretaceous–Eocene the olivine + clinopyroxene cotectic was followed by clinopyroxene + plagioclase ± amphibole. Given the abundance of amphibole and the lack of this mineral in the modern volcanic front, the Cretaceous–Eocene Arc melts were likely more water‐rich than modern Nicaragua, suppressing the crystallization of plagioclase after olivine. We also found temporal changes in element ratios that are sensitive to variations in sediment input. The Cretaceous–Eocene Arc is characterized by a lower Ba/Th compared to the Oligocene–Miocene and modern volcanic front samples, suggesting that the sediment input was lower in Ba, possibly analogous to old deep siliceous sediment subducting in the western Pacific. Both U/Th and U/La are higher in the modern volcanics, reflecting higher U/Th in the subducting sediments following the 'Carbonate Crash'. Finally, we found that the orientation of the arc axis also changed, from northeast‐southwest in the Cretaceous–Eocene to northwest‐southeast after the Oligocene. This change probably records variations in the location of the subduction zone as this region shaped into its current geographic configuration.